COMPARATIVE OF GOVERNANCE IN TERRORISM POLICY IMPLEMENTATION IN INDONESIA AND PHILIPPINES - Ragil Adi Santoso; Wahdah Hazizah; Muhammad Rizky; Silmy Putri Mahandry; Yuan Veriontina Gathari; Mohammad Ichsan Abdillah; Rudiana Rudiana (Jurnal Kebijakan Publik, 2025)
In Southeast Asia, especially in Indonesia and the Philippines, the issue of terrorism has become a major concern because both countries have a long history of terrorism as well as similar geographical and political characteristics. The main objective of this research is to compare the implementation of terrorism policies in Indonesia and the Philippines. This research is a library research with research subjects in the form of research abstracts, articles, websites, books, policies, and other supporting sources. Data analysis refers to the Van Meter and Van Horn model with the stages of reduction, presentation, and conclusion drawing. The instrument used is analytical and descriptive information management so that the author analyzes, interprets, and combines information obtained from various reading sources. The results show that Indonesia combines the hard approach and soft approach, while the Philippines tends to emphasize the hard approach through military force in implementing its policies. Although both have legal frameworks and supporting institutions, there are still challenges in inter-agency coordination and human rights protection. This research concludes the importance of synergy between stakeholders and improvement of regulations in the implementation of terrorism policies between Indonesia and the Philippines that are more fair and preventive in order to increase the effectiveness of the law without violating human rights.